Dry biomass and carbon sequestration in environmental plantings in the Midlands of Tasmania. (30th December 2021) - Davidson, Neil J.; Potts, Brad M.; Burgess, Sebastian; Bailey, Tanya G.
Summary: Estimates of dry biomass and carbon sequestration were made for environmental plantings established in the harsh, dry agricultural landscapes of the Midlands of Tasmania. Plantings were designed to provide habitat connectivity for native wildlife. The dry biomass for 6‐year‐old woodland and riparian plantings was estimated to be 4.7 and 9.0 tonnes/ha, respectively. The carbon component of this biomass was estimated to be 2.4 and 4.5 tonnes/ha carbon, equivalent to 8.7 and 16.5 tonnes/ha carbon dioxide (CO2 ) sequestered, respectively. These are lower than previous estimates for plantings of the same age in the same landscape. This is largely due to lower planting densities of 200 stems/ha, and 883 stems/ha respectively, for woodland and riparian plantings, relative to comparable plantings (˜1, 000 stems/ha). Further, a combination of extreme climatic events during early establishment and high heterogeneity in soil type and landscape position reduced performance in riparian plantings.